Pelatihan Tennis Kids dengan Pendekatan Coaching Games for Understanding Pada Petenis Yunior di Kabupaten Wonogiri: Pelatihan Tennis Kids dengan Pendekatan Coaching Games for Understanding Pada Petenis Yunior di Kabupaten Wonogiri - jarwo, sujarwo (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2026)
The role of partners in the implementation of community service activities has a crucial role. In this Community Service Activity (PKM), the partner who will be the target of the service is the Pelti Wonogiri Regency, which is located at the KONI Wonogiri Regency Office, specifically in the Girimandala GOR Complex. Pelti Wonogiri Regency, as the target of the service, has a crucial function in efforts to foster and develop the potential of athletes in the field of tennis, especially in the Wonogiri Regency area and more broadly in Central Java Province. Currently, one of the sports that shows quite rapid development in Wonogiri Regency is tennis. However, there is a significant imbalance between efforts to cultivate and foster achievement, so effective initial steps are needed, especially for young children, to foster interest and love for this sport. This is expected to encourage them to continue practicing and developing their skills, so that they can compete at a higher level in the future. The training to be implemented is entitled "Tennis Kids Training with a Coaching Games for Understanding Approach for Junior Tennis Players in Wonogiri Regency." This training method will include several stages, namely material delivery, interactive discussions, direct practice, and intensive mentoring. It is hoped that through this training activity, Junior Tennis Players in Wonogiri Regency will experience significant development, thus producing a new generation of tennis athletes capable of competing at a higher level. This regeneration process is expected to produce children who will become the successors of the world of tennis in Wonogiri Regency.